Pediatric Spine Arthrodesis Care Line: reducing SUS ICU daily costs - Pasquini-Netto, Harli; Neves, Kharol; Miyake Okumura, Lucas; Roseira, Allana; Ferreira Matos, Roseli; Muller Avilla, Luiz; Erdmann Bini Cordeiro, Luca; Cavadas da Costa Soares, Leonardo; Campos Ricieri, Marinei; de Araújo Motta, Fabio (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
Objective: To assess the minimization of costs associated with Intensive Care Unit (ICU) length of stay, after implementing a Spinal Arthrodesis Care Pathway (CP). Method: Cost-minimization analysis of administrative CP data from a public pediat ric hospital. Two periods of analysis were considered: pre (2019) and post-complete implementation of the CP (2022). The study considered SUS as payer. The ICU daily cost considered SIGTAP table. A budget impact analysis was conducted considering a 5-year time horizon to estimate a savings associated with more patients receiving CP over the years. Results: 64 patients were followed by PC in 2019 (ICU average time; 3.8 days) and 62 patients (ICU average time: 0.8 days) in 2022, suggesting a 3-day ICU stay reduction, and resulting in minimization of cumulative costs of R$ 189k for 60 patients. In addition, shorter total hospital stay was identified with 2022 CP. Conclusion: The implementation of the Spine Arthrodesis Care Pathway was a strategy considered effective as it provided equal rates as it helped to dis charge patients from hospital and reduced ICU stay. The new CP optimized ICU beds, providing an efficient allocation of resources in a hospital from SUS.